Serum Gamma-Glutamyltransferase, Daily Alcohol Consumption, and the Risk of Chronic Kidney Disease: The Kansai Healthcare Study - Mikiko Shibata; Kyoko Kogawa Sato; Shinichiro Uehara; Hideo Koh; Keiko Oue; Hiroshi Kambe; Michio Morimoto; Tomoshige Hayashi (Journal of Epidemiology, 2020)
Background: Serum gamma-glutamyltransferase has been recognized as the risk factor of cardiovascular and metabolic diseases. However, the association between serum gamma-glutamyltransferase and the risk of chronic kidney disease is not well known, and no prospective studies have examined separately the relationship of serum gamma-glutamyltransferase with the risk of proteinuria versus that of low estimated glomerular filtration rate (eGFR). Methods: We prospectively followed 9,341 Japanese men who did not have low eGFR, proteinuria, or diabetes, and did not take antihypertensive medications at entry for the analysis of proteinuria, and we followed 9,299 men for the analysis of low eGFR. We defined “persistent proteinuria” as proteinuria detected two or more times consecutively and persistently as ≥1+ on urine dipstick at the annual check-up until the end of follow-up. Low eGFR was defined as eGFR <60 mL/min/1.73 m2. Results: During the 11-year observation period, 151 men developed persistent proteinuria and 1,276 men developed low eGFR. In multivariate models, the highest quartile (≥71 IU/L) of serum gamma-glutamyltransferase was independently related to the development of persistent proteinuria (hazard ratio 3.39; 95% confidence interval, 1.92–5.97) compared with the lowest quartile (≤25 IU/L). In joint analysis of alcohol consumption and serum gamma-glutamyltransferase, non-drinkers in the highest tertile (≥58 IU/L) of serum gamma-glutamyltransferase had the highest risk of persistent proteinuria. However, there was no association between serum gamma-glutamyltransferase and low eGFR. Conclusion: In middle-aged Japanese men, elevated serum gamma-glutamyltransferase was independently associated with future persistent proteinuria, but not with low eGFR.